Mechanical haemolytic anaemia after valve repair operations for non-rheumatic mitral regurgitation. Issue 4 (October 1980) - Warnes, C; Honey, M; Brooks, N; Davies, J; Gorman, A; Parker, N
Abstract : Two cases are described in which severe mechanical haemolytic anaemia developed shortly after operation for repair of non-rheumatic mitral regurgitation. One patient had a "floppy" valve and the other cleft mitral leaflets, and both had chordal rupture. In both there was residual regurgitation after repair though in one this was initially only trivial. Clinically manifest haemolysis ceased after replacement of the valve by a frame-mounted xenograft. There are two previously reported cases in which haemolytic anaemia followed an unsuccessful mitral valve repair operation. Subclinical haemolysis or mild haemolytic anaemia may occur with unoperated valve lesions, but hitherto frank haemolytic anaemia has been observed only when turbulent blood flow is associated with the presence of a prosthetic valve or patch of prosthetic fabric. In these four cases, however, polyester or Teflon sutures were the only foreign material, and it is suggested that when these are used for the repair of leaflets, particularly in non-rheumatic mitral valve disease, they may increase the damaging effect of turbulence on circulating red blood cells.